Measuring the Cultural Impact of Sustainable Marketing on Branding: An Analytical Survey of the Opinions of a Sample of Physicians, Administrators, and Technicians Working in Private Hospitals in the Center of Maysan Governorate - Hatem Sultan, Karrar; Hamid Ismail, Amjad (Iraqi Journal for Administrative Sciences, 2026)
This research aimed to measure the impact of the cultural dimension of sustainable marketing on branding by targeting private hospitals in the center of Maysan Governorate. These hospitals have limited attention to considering cultural aspects in their marketing practices, resulting in weak brand strength. A sample of 136 employees was selected, comprising doctors, administrators, and technicians. The study adopted a descriptive-analytical approach, collecting data using a questionnaire. Data was analyzed using the statistical tools available in SPSS software, namely means and standard deviations. The results showed a statistically significant positive correlation between the cultural dimension of sustainable marketing and branding, specifically in its dimensions of brand awareness, brand loyalty, brand image, and perceived quality. The research's significance lies in highlighting the active role of the cultural dimension in strengthening hospital brands, thereby contributing to improved patient loyalty. The research recommends the necessity of emphasizing the consideration of values, customs, traditions, and privacy in the provision of medical services, and establishing training programs to raise the level of cultural awareness. Among the employees, which contributes to strengthening its brand and achieving a competitive advantage.